Eurasian Declaration on Human and Peoples’ Rights – Continental Human Rights Document of Century: Formulation of the Problem - BUSURMANOV, Zhumabek; AMANDYKOVA, Saule Koshkenovna; SAIMOVA, Sholpan Altynbekovna; KHAIRMUKHANMEDOV, Nurbek; ZHUMANOVA, Maira (Journal of Advanced Research in Law and Economics, 2017)
Eurasian Economic Union is one of the most ambitious projects of integration of the XXI century. In the long term, well thought-out and effectively implemented social policies of the Union will give it a special humanistic value. The unity of the same views on the issue of human rights will contribute to the formation of the Eurasian concept of human rights, which can lead to the need for Eurasian Declaration of Human Rights and Peoples' Rights as a new human rights instrument of the Eurasian continent. Creation of the Eurasian Court of Human Rights as a political and legal institution will allow protecting the violated human rights, taking into account the features of the Eurasian continent.